HUBUNGAN KOORDINASI MATA–TANGAN DAN KELINCAHAN TERHADAP KETERAMPILAN GROUNDSTROKE PADA PEMAIN TENIS PEMULA - Fadjri, Mukharrar; Fransiskus Rumthe; Emayanti Anggraeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between eye-hand coordination and agility on groundstroke skills in beginner tennis players. The research method used is a quantitative approach with a correlational design. The research subjects consisted of 30 beginner tennis players selected using purposive sampling. The independent variables in this study were eye-hand coordination and agility, while the dependent variable was groundstroke skills. The instruments used included a ball throw-catch test against a wall to measure hand-eye coordination, the Illinois Agility Test to measure agility, and forehand and backhand accuracy tests to measure groundstroke skills. Data analysis was performed using descriptive statistics, Pearson Product Moment correlation test, and multiple regression analysis. The results showed a significant positive relationship between hand-eye coordination and groundstroke skills (r = 0.62; p < 0.05) and a significant negative relationship between agility and groundstroke skills (r = −0.58; p < 0.05). The multiple regression results showed that eye-hand coordination and agility simultaneously contributed significantly to groundstroke skills with a coefficient of determination of 54%. Thus, it can be concluded that eye-hand coordination and agility are important factors that influence groundstroke skills in tennis players.